Market-based low carbon retrofit in social housing: insights from Greater Manchester - Cauvain, Jenni; Karvonen, Andrew; Petrova, Saska (Taylor & Francis, 2018)
In recent years, social housing providers in the UK have become influential actors in realising the national government’s decarbonisation agenda. However, when decarbonisation is considered in light of austerity measures and privatisation of public housing, a number of contradictions arise. From interviews and a workshop with policymakers and registered providers in the city-region of Greater Manchester, three tensions are highlighted. First, since the 1980s, the housing stock condition has been used as a political pawn in successive reforms to demunicipalize social housing. Second, local authorities continue to harness the collectivities that remain in the social housing sector to realise their decarbonisation goals. Third, the retrofit practices of social landlords are only superficially aiming for carbon control, instead they focus on the social aims that are seen as important to the ethos and business model of the landlord. The paper concludes that there are unavoidable conflicts between the interests of different actors whose low carbon economy is conceived at different spatial scales and with different underlying objectives. As social landlords are foregrounded in sub-regional low carbon policy, they are effectively co-opted into market-based retrofit, resulting in unintended consequences for the social housing sector.